It's not fiction, it is fact: tensions between instrument and object a study about the use of cinema in education - Arlete Cipolini; Amaury Cesar Moraes (Universidade Federal de Santa Maria, 2015)
This dissertation aims at discussing the relationship between the school and the use of audiovisuals, mainly, cinema. The starting point is that even though schools are more equipped than ever, the insertion of the cinema in schools is not effective. With the advance of technology and the improvement of audiovisual equipments, nowadays, great movie productions are accessible to most part of the population through VHS and DVD. Such growth seemed to be ignored by schools, and it is noticed that public administrations publicize largely that schools are equipped with the necessary equipments for the reproduction of films, but with no preoccupation when it comes to the courses for teachers and educators for the task. This piece of work also discusses the historical importance of the language and its way of cumulated historical knowledge to be transmitted by the school to its members. The hypothesis of this dissertation that movie language besides being a pedagogical tool is also a knowledge tool that allows a broader perception of reality, and that the courses for teachers do not prepare the professionals for an adequate use of this resource and its language were confirmed during the research, leading to the conclusion that the school still uses new languages, technologies and knowledge in a disjointed, inadequate and insufficient ways that leads to inferior results that could be achieved through the effective use of these languages, technologies and knowledge.